Peran Irigasi Klorheksidin Pada Perawatan Penyakit Periodontal - Ricky Anggara Putranto (Jurnal Kedokteran Gigi Terpadu, 2019)
Background: Chlorhexidine gluconate is a bactericidal agent that is effective in dental practice as an antiplaque agent that is very good in oral hygiene. Plaque microorganisms are the primary etiological factors associated with periodontal disease which must be eliminated consistently as a preventive measure. Many chemical agents that have been evaluated to determine their effect on plaque, gingivitis and periodontitis, one of which is chlorhexidine, has been successfully introduced and studied extensively. Chlorhexidine has been used to supplement, not replace mechanical therapy. This study aims to describe the role of chlorhexidine supragingivally and subgingival irrigation in periodontal disease. Treatment of periodontal pockets with chlorhexidine irrigation in addition to scaling and root smoothing, provides a significant increase in reducing pocket depth and microbial count. Irrigation of chlorhexidine solution is effective in the treatment of periodontitis. This is probably due to its ability to maintain a chlorhexidine concentration that is biologically significant for sufficient time in the periodontal pocket. Conclusions: Chlorhexidine is an antiplaque agent and has excellent antimicrobial properties. Local applications with irrigation or mouthwash depend on high initial concentrations and repeated applications to provide sustained effectiveness. Modification of microflora in the periodontal pocket can be treated with irrigation of chlorhexidine.